Climate change, air pollution, and allergic respiratory diseases: a call to action for health professionals - Shi-Zhou Deng; Bin B. Jalaludin; Josep M. Antó; Jeremy J. Hess; Cun-Rui Huang; Li-Shao Guo (Chinese Medical Journal, 2020)
Abstract. Rising emissions of greenhouse gases in the atmosphere have warmed the planet substantially and are also accompanied by poor air quality. The increased prevalence of allergic airway disease worldwide can be partially attributed to those global environmental changes. Climate change and air pollution pose adverse impacts on respiratory allergies, and that the mechanisms are complex and interactive. Adverse weather conditions, such as extreme temperatures, can act directly on the respiratory tract to induce allergic respiratory illnesses. Thunderstorms and floods can alter the production and distribution of aeroallergens while wildfires and dust storms increase air pollution, and therefore indirectly enhance health risks. Concentrations of particulate matter and ozone in the air have been projected to increase with climate warming and air stagnation, and the rising temperatures and CO2 increase pollen, molds, and spores, which escalate the risk of allergic respiratory diseases. The synergistic effects of extreme heat and aeroallergens intensify the toxic effect of air pollutants, which in turn augment the allergenicity of aeroallergens. With the Earth's climate change, migration of humans and plants shift the living environments and allergens of susceptible people. Urban residents are exposed to multiple factors while children are sensitive to environmental exposure. Since climate change may pose many unexpected and persistent effects on allergic respiratory diseases, health professionals should advocate for effective mitigation and adaptation strategies to minimize its respiratory health effects.